Imag(in)ing otherness : filmic visions of living together - Plate, S. Brent, 1966-; Jasper, David (American Academy of Religion cultural criticism series, 1999)
Imag(in)ing Otherness explores relationships between film and religion, aesthetics and ethics. The volume examines these relationships by viewing how otherness is imaged in film and how otherness alternately might be imagined. Drawing from a variety of films from differing religious perspectives--including Chan Buddhism, Hinduism, Native American religions, Christianity, and Judaism--the essays gathered in this volume examine the particular problems of "living together" when faced with the tensions brought out through the otherness of differing sexualities, ethnicities, genders, reli